In need of clarification: Current perceptions of impact investing in the German and Swiss foundation sectors - Sara Stühlinger (University of Basel, Center for Philanthropy Studies (CEPS), 2018)
Impact investing is increasingly becoming an omnipresent topic. Anglo-American practices are spilling over into continental Europe's foundation sector. However, there are still few studies focusing on foundations as impact investors. This study uses 16 semi-structured interviews with foundation representatives and intermediaries to examine their views on impact investing. A framework based on different understandings of impact investing is developed. Depending on the segment of impact investing, distinct challenges arise in the areas of leadership, legal requirements, and availability of investment opportunities. The interviews also raise normative questions. The study shows that impact investing changes institutional logics in foundation management.
Keywords: 330; expert interviews; foundations; impact investing; institutional logics